2019
DOI: 10.31703/grr.2019(iv-i).06
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Ideologies through Textbooks: A Study of Khyber Pakhtunkhwa English Textbooks

Abstract: The main purpose of the study is to highlight the ideological representation of an Islamic state, Pakistan along with leadership mindset in the textbook. It is a discourse study of the prescribed English textbook used as a core teaching material at intermediate level in Khyber Pakhtunkhwa (KP), Pakistan. The researcher has analyzed various extracts and taken different lessons from the textbook of English compulsory taught at second year in the intermediate level. The study has used the Fairclough’s Critical Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The research shows how the Vietnamese authorities have deliberately manipulated textbook content as a means of promoting national unification. In contrast, Ali, Hassan, and Hanan (2019) have perceived ideology in EFL textbooks in Pakistan as a positive force that may make people more patriotic, peaceful, courteous, civilized, educated, and more social.…”
Section: Resultsmentioning
confidence: 97%
“…The research shows how the Vietnamese authorities have deliberately manipulated textbook content as a means of promoting national unification. In contrast, Ali, Hassan, and Hanan (2019) have perceived ideology in EFL textbooks in Pakistan as a positive force that may make people more patriotic, peaceful, courteous, civilized, educated, and more social.…”
Section: Resultsmentioning
confidence: 97%
“…5. Ali, A., Hassan, S., & Hanan, F. (2019). Propagation of ideologies through textbooks: A study of Khyber Pakhtunkhwa English textbooks.…”
Section: Methodsmentioning
confidence: 99%
“…They believed that the Pakistani education system, especially its textbook regime, had to rethink its narrative of what women do, can do and should do. The participants read the research articles shared with them (Ahmad & Shah 2019;A. Ali, Hassan, & Hanan 2019;R.…”
Section: Female Representation In Textbooksmentioning
confidence: 99%
“…Moreover, there are several studies have been conducted looking into this topic across many different areas of study. In one study Ali et al, (2017) concluded that general science textbooks for grades VI-VIII lacked higher-order thinking questions and activities. The remedy to this the study said, was to include more critical thinking-oriented content in the books to enhance students' cognitive skills.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%